Técnica autorradiográfica para investigação geológica - Estudo de caso na área do projeto rio preto - Duarte, Cynthia Romariz; Bonotto, Daniel Marcos [UNESP] (My University, 2005)
The auto-radiography is a photographic method to registrate in sensitive emulsion the spatial distribution a rays emitted by radioisotopes of a sample or an object. The auto-radiography was applied to detect the presence of radioactive minerals in some samples of schists and gneisses from the Ticunzal Formation, Northeast Goiás State, aiming to implement the use of this technique in LABIDRO - Hydrochemistry and Isotopes Laboratory of the Department of Petrology and Metallogenesis, State University of São Paulo/Campus of Rio Claro.
Autoradiographic technique for geological investigation - Case study in Rio Preto Project area
Keywords: Auto-radiography; Ticunzal Formation; emulsion; gneiss; photogrammetry; radio wave; radiography; radionuclide; schist; spatial distribution; Brazil; Goias; Minas Gerais; Rio Preto State Park; South America